Superovulation of Bovine Females: Alternatives to Reduce the Number of fsh Injections: alternativas para reducir el número de inyecciones de FSH - Mogollón Waltero, Édgar Mauricio; Burla Dias, Angelo Jose (Spei Domus, 2013)
Improvements in reproductive efficiency and the multiplica-tion of more productive genotypes are directly linked to increases inproductivity, which are decisive factors for livestock sustainability. Re-search in this field thus proposes embryo transfer (et) as a basic biote-chnological tool to increase the quantity and quality of cattle produced.The conventional process of superovulation for embryo transfer in cattle uses eight applications of follicle stimulating hormone (fsh) with 12 hour intervals. This procedure increases the handling and stress of these animals, which can adversely affect the results. The aim of this review is to compile the most marked examples of progress in research over the past two decades focused on reducing the number of fsh applications. Different strategies have been used, ranging from the simple subcutaneous hormone application to transport and controlled release through electronic devices placed in the reproductive tract, as well as vehiculization of polymeric substances to control release into the bloodstream. We conclude that these advances will certainly revolutionize the cattle industry and positively influence massive use of embryonic biotechnologies which, for obvious reasons, will facilitate genetic improvements in shorter time spans within bovine herds.